Political practices of transformation of East and Southeast Asia countries - Тесленко, Сергій Сергійович; Тесленко, С. С.; Тесленко, Сергей Сергеевич; Teslenko, Serhii S. (Одеса : Видавничий дім «Гельветика», 2021)
The article considers models of political transformation in East Asian countries.The analysis of political practices of transformation of the countries of East and South-East Asia is carried out in the study. The research contains the factors that influenced the successful implementation of modernization projects in the states of the region. The specific features of the political transformations of the states of the region associated with the formation of non-Western democracies on the basis of “development authoritarianisms” are revealed.Carrying out large-scale transformations is connected with the need to establish sovereignty in the postcolonial period and ensure national security in the current geopolitical conditions. The success of the East Asian model of transformation is also associated with the preservation of elements of traditional regulation, a unique synthesis of traditions and innovations based on a special, synthetic way, non-Western and non-mobilization type.Governments and national leaders play a special role in the political practices of non-Western modernization, ensuring the planning of modernization strategies. A separate role in the transformation belongs to the competent bureaucracy with a minimum degree of corruption. And the transformations were carried out by authoritarian methods.Non-Western modernization is of interest both from a theoretical and empirical point of view, especially given the effect of the non-Western approach to transformation, embodied in the so-called Asian economic miracle and contributing to national consolidation in Southeast and East Asia.For developing countries, it is important to choose the ways of their socio-political and economic development, especially in the context of globalization. The study of the experience of the countries of Southeast and East Asia allows us to identify the main directions of their development that have transformed societies, and to determine an acceptable development strategy for the state.Back in the 1990s, concepts were put forward according to which the 21st century would be the era of domination of the Asia-Pacific civilization, which replaces the Euro-Atlantic one. The modernization of the countries of Southeast Asia is becoming a factor in reformatting the established world order, creating a new balance of power in the international arena and new centres of influence in political and economic relations.

У статті розглядаються моделі політичної трансформації в східноазійських державах. Здійснено аналіз політичних практик трансформації країн Східної та Південно-Східної Азії; досліджено чинники, що вплинули на успішну реалізацію модернізаційних проєктів у державах регіону; виявлено специфічні риси політичних трансформацій держав регіону, пов’язані з формуванням незахідних демократій на основі «авторитаризмів розвитку». Проведення широкомасштабних перетворень пов’язане з необхідністю утвердження суверенітету в постколоніальний період і забезпечення національної безпеки у сучасних геополітичних умовах. Успіх східноазійської моделі трансформації зв’язується також зі збереженням елементів традиційної регуляції, унікальним синтезом традицій і новацій на основі особливого, синтетичного шляху, незахідного і немобілізаціонного типу. В політичних практиках незахідної модернізації особливу роль відіграють уряди і національні лідери, що забезпечують планування стратегії модернізації. Окрема роль у перетвореннях належить компетентній бюрократії з мінімальним ступенем корупції. А перетворення здійснені авторитарними методами. Незахідна модернізація становить інтерес як з теоретичної, так і з емпіричної точок зору, особливо з огляду на ефект від незахідного підходу до трансформації, що втілився у так званому азійському економічному диві та сприяв національній консолідації у країнах Південно-Східної та Східної Азії. Для країн, що розвиваються, важливим є вибір шляхів їх соціально-політичного і економічного розвитку, особливо в умовах світової глобалізації. Вивчення досвіду країн Південно-Східної та Східної Азії дозволяє виявити основні напрями їх розвитку, що трансформували суспільства, і визначити прийнятну для держави стратегію розвитку. Ще у 1990-х роках були висунуті концепції, згідно з якими XXI століття стане епохою домінування Азійсько-тихоокеанської цивілізації, яка йде на зміну Євроатлантичній. Модернізація країн Півден-но-Східної Азії стає фактором переформатування усталеного світоустрою, створюючи новий баланс сил на міжнародній арені і нові центри впливу в політичному та економічному відношеннях.

В статье рассматриваются модели политической трансформации в восточноазиатских странах. Осуществлен анализ политических практик трансформации стран Восточной и Юго-Восточной Азии; исследованы факторы, повлиявшие на успешную реализацию модернизационных проектов в государствах региона; выявлены специфические черты политических трансформаций государств региона, связанные с формированием незападных демократий на основе «авторитаризмов развития». Проведение широкомасштабных преобразований связано с необходимостью утверждения суверенитета в постколониальный период и обеспечения национальной безопасности в современных геополитических условиях. Успех восточной модели трансформации связывается также с сохранением элементов традиционной регуляции, уникальным синтезом традиций и новаций на основе особого, синтетического пути, незападного и немобилизационного типа. В политических практиках незападной модернизации особую роль играют правительства и национальные лидеры, которые обеспечивают планирование стратегии модернизации. Отдельная роль в преобразованиях принадлежит компетентной бюрократии с минимальной степенью коррупции. А преобразования осуществлены авторитарными методами. Незападная модернизация представляет интерес как с теоретической, так и с эмпирической точек зрения, особенно учитывая эффект от незападного подхода к трансформации, который воплотился в так называемом азиатском экономическом чуде и способствовал национальной консолидации в странах Юго-Восточной и Восточной Азии. Для развивающихся стран, важным является выбор путей их социально-политического и экономического развития, особенно в условиях мировой глобализации. Изучение опыта стран Юго-Восточной и Восточной Азии позволяет выявить основные направления их развития, что трансформировали общества, и определить приемлемую для государства стратегию развития. Еще в 1990-х годах были выдвинуты концепции, согласно которым XXI век станет эпохой доминирования Азиатско-тихоокеанской цивилизации, которая идет на смену Евроатлантической. Модернизация стран Южно-но-Восточной Азии становится фактором переформатирования устоявшегося миропорядка, создавая новый баланс сил на международной арене и новые центры влияния в политических и экономических отношениях.
Teslenko S. S. Political practices of transformation of East and Southeast Asia countries / S. S. Teslenko // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. редкол.), Л. І. Кормич (голов. ред.), І. М. Милосердна (відп. ред.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Видавничий дім «Гельветика», 2021. – Вип. 67. – С. 118-124.
Keywords: political transformation; Southeast Asia; political process; non-Western democracies; authoritarianism; political culture; політична трансформація; Південно-Східна Азія; політичний процес; незахідні демократії; авторитаризм; політична культура; политическая трансформация; Юго-Восточная Азия; политический процесс; незападные демократии; авторитаризм; политическая культура; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science